Respiratory Epithelium Lined Cyst of the Maxilla: Differential Diagnosis - C. P. Martinelli-Kläy; S. Chatelain; F. Salvado; T. Lombardi (Case Reports in Pathology)
Maxillary cysts, including the cysts lined by respiratory epithelium, can present a diagnostic challenge. We report an unusual case of a maxillary cyst on an endodontically treated tooth #16, in which the cavity was totally lined by a respiratory epithelium. The patient, a 35-year-old male, presented with a generalized chronic periodontitis and complained of a pain in the tooth #16 region. A periodontal pocket extending to the root apices with pus coming out from the gingival was found. A combined endodontic periodontal was observed on a panoramic radiography. CBCT-scan revealed a well-circumscribed radiolucent lesion at the apices of the distobuccal root of the 16. A communication with the right maxillary sinus cavity and a maxillary and ethmoidal sinusitis were also observed. The lesion was removed and histological examination revealed a cyst lined exclusively by respiratory epithelium. Ciliated and rare mucous cells were also observed. The diagnosis could evoke a surgical ciliated cyst mimicking the radicular cyst but the patient has no previous history of trauma or surgery in the maxillofacial region. It could also be an unusual radicular cyst in which the stratified squamous epithelium was destroyed by inflammation and replaced by a respiratory epithelium of the maxillary sinus.